Astute competition the economics of strategic diversity - Johnson, Peter, 1956- (Elsevier B. V., 2006)
This book is embedded in practical tools which proposes a fourth field of economics in addition to macro, micro and industrial organisation economics (IO); namely what may be called the economics of diversity. This book asserts that businesses are as individual as people. All have unique identities, what may be called genomes. As such economic diversity is the norm, rather than the economics of commodities. Contemporary economics deals very effectively with commodities in situations of perfect competition. It also makes some useful insights into imperfect competition and monopoly. The first half of the book expands the conceptual underpinnings of the economics of diversity (ecosystems, business models, advantage, rents and valuation of resources); the second half demonstrates how these methods can be practically applied through tools and techniques to deal with questions of business development, corporate strategy, mergers and acquisitions, and start-ups.
Includes index.
Keywords: Strategic planning.; Business planning.; Competition -- Management.; elektronické knihy; electronic books